Constitutively active RhoA inhibits proliferation by retarding G(1) to S phase cell cycle progression and impairing cytokinesis - Morin, Pierre (2009)
The actions of RhoA in cytoskeletal regulation have been extensively studied. RhoA also contributes to proliferation and oncogenic transformation by less well-characterized means. Elevated RhoA signalling has been associated with human cancer; through increased RhoA expression, mutation or elevated expression of activating Rho guanine-nucleotide exchange factors (GEFs), or from deletion or decreased expression of inhibitory Rho GTPase-activating proteins (GAPs). Unlike the Ras oncogene, constitutively-activated GTPase-deficient RhoA mutants have not been identified in tumours. To investigate the effects of active RhoA on proliferation, we generated Swiss3T3 cells that inducibly express wild-type RhoA or GTPase-deficient active V14RhoA. We found that V14RhoA inhibited cell proliferation by retarding entry into the DNA synthetic cell cycle phase and blocking successful completion of cytokinesis, resulting in an increased incidence of binucleate cells. These effects were associated with inhibition of mitogen-induced activation of the MAPK pathway, and suppression of several proteins involved in mitosis, including anillin, ECT2 and cyclin B1 which would be expected to result in reduced activation of endogenous RhoA at the cell equator. Accumulation of active RhoA protein in the midbody of cells in telophase was inhibited in V14RhoA-expressing cells, suggesting that RhoA inactivation must occur prior to re-activation. Defective cytokinesis was also associated with prominent actin structures in V14RhoA-expressing cells, which might be incompatible with equatorial furrowing. Using super-resolution imaging based on single-molecule switching, we have significantly improved the resolution of active RhoA in midbodies. These results indicate that constitutively-active RhoA antagonizes several cellular activities that contribute to proliferation, highlighting the importance for cycling between GTP/GDP-bound states.